Hubungan antara Self Efficacy Pengambilan Keputusan Karir dengan Perencanaan Karir pada Siswa SMK N 1 Klego Boyolali - Wahyuningsih, Diana Dewi; Setyo Nugroho, Imam; Rahmalih, Renata; Khoiry, Hafizh (JURNAL BIMBINGAN KONSELING FLOBAMORA, 2025)
The type of research is correlational which aims to determine the significance of the relationship between self-efficacy in career decision making and career planning in class XII students of SMK N 1 Klego Boyolali. The type of research used in this study is quantitative correlational research. The research sample was all class XII students of SMK N 1 Klego Boyolali totaling 264 students, divided into 5 majors, namely: mechanical engineering, electrical installation engineering, fashion design, construction and property business and building drawing information design. The sampling technique used cluster random sampling technique. Data collection used 2 instruments, namely: career decision making self-efficacy scale (25 items, α = 0.869) and career planning scale (24 items, α = 0.885). Hypothesis testing in this study used regression analysis techniques. Based on the regression correlation test, the rxy value was obtained = 0.593; with Þ=0.000 (Þ<0.05), so there is a positive relationship between self-efficacy in career decision making and career planning in grade XII students of SMK N 1 Klego Boyolali. This means that self-efficacy in career decision making contributes 35.1% to career planning. The results of this study are very relevant because they can strengthen theoretical studies and phenomena of the relationship between self-efficacy variables in career decision making and career planning. Further research recommendations can test the correlation of self-efficacy in career decision making with different variables.